Kinematic and dynamic analysis of lower-mobility cooperative arms. Issue 9 (1st May 2014) - Long, Philip; Khalil, Wisama; Caro, Stéphane
SUMMARY: This paper studies the modeling and analysis of a system with two cooperative manipulators working together on a common task. The task is defined as the transportation of an object in space. The cooperative system is the dual-arm of the humanoid robot Nao, where the serial architecture of each arm has 5 degrees of freedom. The kinematics representing the closed chain system is studied. The mobility of the closed-loop system is analyzed and the nature of the possible motions explored. The stiffness of some motors can be reduced until they behave as passive joints. Certain joints are then chosen as actuated (independent) and the others as passive (dependent). The serial and parallel singular configurations of the system are considered. From the kinematic analysis, admissible and inadmissible minimum actuation schemes are analyzed. Furthermore the dynamic performance of the schemes is compared to find the optimum minimum actuation scheme.